Analisis Nilai-Nilai Karakter Dalam Buku Cerita Rakyat Sang Piatu Menjadi Raja Dari Daerah Bengkulu - Ottey Zul Apriani; Wurjinem Wurjinem; Sri Ken Kustianti (Universitas Bengkulu, 2021)
This research aims to analyse the values of characters in the folklore of the orphans to become king of the Bengkulu area the method in use is a qualitative method of descriptive analysis. The research Data is the folklore of the people who become kings. Collection with library studies. The analytical techniques used are Conten analysis (content analysis). The results of the research in the folklore of the people to be obtained as a king of twelve values of religious character, honest, discipline, hard work, creative, independent, curiosity, achievement, responsibility, love peace, environmental care, social care, and friendly/communicative.